Alastair Nicholson address at the National Press Club on 4 August 1993 - Nicholson, Alastair, 1938-; Australia. Family Court; National Press Club (Australia) (1993)
Hon. Alastair Nicholson, Chief Justice of the Family Court of Australia, speaks about Australian family law; the operation of the Family Court; the changing nature of family relationships; and the failure of governments to recognise increasing family problems.
Copies available on cassette.
Photographs available.
Also available online
Transcript available (typescript, 32 leaves)
Keywords: Australia. -- Family Court; Australia; Family law -- Australia